2014
DOI: 10.1186/1472-6920-14-100
|View full text |Cite
|
Sign up to set email alerts
|

The DREEM, part 2: psychometric properties in an osteopathic student population

Abstract: BackgroundThe Dundee Ready Educational Environment Measure (DREEM) is widely used to assess the educational environment in health professional education programs. A number of authors have identified issues with the psychometric properties of the DREEM. Part 1 of this series of papers presented the quantitative data obtained from the DREEM in the context of an Australian osteopathy program. The present study used both classical test theory and item response theory to investigate the DREEM psychometric propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
2
16
1
Order By: Relevance
“…It is possible, contrary to previous claims made by the DREEM developers, 22 that the inventory might not be independent of culture, a viewpoint supported by others. 24,40,81 On the contrary, both in 2009 and 2012, our data revealed that students demonstrated disagreement with the statement ''The teachers get angry in class,'' displaying scores above the estimated mean and greater than the cutoff for strong areas. Nevertheless, the notion of authoritarianism could form an accurate assessment of the students' perception and must be investigated further.…”
Section: Authoritarian Teacherscontrasting
confidence: 54%
See 3 more Smart Citations
“…It is possible, contrary to previous claims made by the DREEM developers, 22 that the inventory might not be independent of culture, a viewpoint supported by others. 24,40,81 On the contrary, both in 2009 and 2012, our data revealed that students demonstrated disagreement with the statement ''The teachers get angry in class,'' displaying scores above the estimated mean and greater than the cutoff for strong areas. Nevertheless, the notion of authoritarianism could form an accurate assessment of the students' perception and must be investigated further.…”
Section: Authoritarian Teacherscontrasting
confidence: 54%
“…Consequently, some recent concerns have surfaced about the psychometric robustness of the DREEM instrument. 24,[38][39][40] Although the DREEM instrument was initially reported to have good construct validity in its Figure 2 -The figure depicts the relationship between educational environment issues and negative perceptions. A teacher-centered approach, with teachers taking on traditional roles in student-centered curricula, could promote teaching that emphasizes factual overload, thus resulting in a stressful environment for students.…”
Section: Methodological Reflections and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, the DREEM inventory has demonstrated itself globally valuable in a diverse health-care setting such as medical, dental, nursing, and chiropractic the teaching-learning environments [16][17][18][19][20]. The far majority these studies revealed that "variety of descriptive statistics for the scale items, subscales, and the total DREEM score; internal consistency (Cronbach's alpha); and correlational statistics, investigating relationships between the DREEM total and subscale scores with characteristics such as age, gender, and program year level" [21].…”
Section: Introductionmentioning
confidence: 99%